Examen Especial a Activos Financieros e Inventarios de la Compañía Ecolac Cía. Ltda., de Loja, periodo de enero a diciembre 2021. - Balcázar Villacis, Yuliana Anahí (2024)
The following work is titled: An Examination of the Financial Assets and Inventories of Ecolac C.A., of Loja for the period between January and December 2021. The main objective of the study was to determine whether the balances of the accounts examined were reasonable. Accordingly, an internal control system evaluation has been carried out for the purpose of assessing the level of confidence and risk, and a reasonableness assessment of the financial statements has been made. As part of the preparation of the statement of financial position in this case, which includes the values of the Financial Assets and Inventories, the company will also draft a special examination report containing comments, conclusions and recommendations relating to the development of the special examination in Ecolac Cía. For this purpose, the achievement of the objectives, the methodology implemented and the development of the three phases of the special examination were taken into consideration. Phase 1 Planning included the preparation of the pre-visit guide, the preliminary planning report, the preliminary risk assessment matrix, as well as the specific planning report, in order to gain a better understanding of the company itself and the management of its resources. As a result of the evaluation of the internal control system, the Financial Assets and Inventory were found to be low risk and the level of confidence in the inventory was high. The team leader and the operative auditor also created working papers that explained their work. As a final step, the special examination report contained a number of weaknesses such as the failure to initiate and conduct a collection process in a timely manner, the lack of a procedural manual, among others.